2014
DOI: 10.1590/s1983-40632014000400010
|View full text |Cite
|
Sign up to set email alerts
|

Respostas de genótipos de palma forrageira a diferentes densidades de cultivo

Abstract: Considerando-se a importância da palma forrageira como alternativa alimentícia para os rebanhos do semiárido brasileiro e o efeito do espaçamento de cultivo entre plantas, este estudo objetivou avaliar a morfometria, produtividade e composição químico-bromatológica de genótipos de palma forrageira, em diferentes densidades de cultivo. O delineamento experimental utilizado foi em blocos completos casualizados, em esquema fatorial 3x4. Os tratamentos constituíram-se da combinação de três genótipos de palma forra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
3
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 17 publications
1
27
3
19
Order By: Relevance
“…In evaluation of plant densities in Opuntia and Nopalea, Cavalcante et al (2014) observed that increasing plant density reduced number of cladodes per plant, length and width of cladodes; however, there was increase in DM productivity, accumulation of water and nutrients per area. Silva et al (2014) tested plant densities ranging between 10,000 and 80,000 plants ha -1 and observed that in which: Y ijklm = represents the mean response of site i, in the block j, N fertilization k, P fertilization l and plant density m; µ = population mean; Si = site effect; b j = block effect; ε ijklm = random error; N l = N fertilization effect; P k = N fertilization effect; D m = plant density effect; (SN) ik = interaction effect between site and N fertilization; (SP) il = interaction effect between site and P fertilization; (SD) im = interaction effect between site and plant density; (NP) kl = interaction effect between N fertilization and P fertilization; (ND) km = interaction effect between N fertilization and plant density; (PD) lm = interaction effect between P fertilization and plant density; (SNPD) iklm = interaction effect between site, N fertilization, P fertilization and plant density.…”
Section: Resultsmentioning
confidence: 97%
“…In evaluation of plant densities in Opuntia and Nopalea, Cavalcante et al (2014) observed that increasing plant density reduced number of cladodes per plant, length and width of cladodes; however, there was increase in DM productivity, accumulation of water and nutrients per area. Silva et al (2014) tested plant densities ranging between 10,000 and 80,000 plants ha -1 and observed that in which: Y ijklm = represents the mean response of site i, in the block j, N fertilization k, P fertilization l and plant density m; µ = population mean; Si = site effect; b j = block effect; ε ijklm = random error; N l = N fertilization effect; P k = N fertilization effect; D m = plant density effect; (SN) ik = interaction effect between site and N fertilization; (SP) il = interaction effect between site and P fertilization; (SD) im = interaction effect between site and plant density; (NP) kl = interaction effect between N fertilization and P fertilization; (ND) km = interaction effect between N fertilization and plant density; (PD) lm = interaction effect between P fertilization and plant density; (SNPD) iklm = interaction effect between site, N fertilization, P fertilization and plant density.…”
Section: Resultsmentioning
confidence: 97%
“…Na comparação entre os genótipos, os resultados divergiram dos apresentados por Cavalcante et al (2014) que avaliaram as respostas produtivas de genótipos de palma forrageira e verificaram maior produtividade para a Miúda (Nopalea) em relação a Gigante e Redonda (Opuntia). Por outro lado, Silva et al (2015) observaram melhor resposta produtiva da OEM (Opuntia) quando comparada com a IPA Sertânia e com a Miúda (Nopalea), resultado semelhante ao encontrado na presente pesquisa, em que a OEM teve maior MF que a Miúda.…”
Section: Massa De Forragem T De Mv/haunclassified
“…O maior número de cladódios na palma Miúda em comparação com a Redonda e a Gigante foi verificado e relatado por Cavalcante et al (2014) no município de Frei Paulo/SE. Enquanto as palmas Redonda e Gigante apresentaram 16 e 17 cladódios/planta, respectivamente, a palma Miúda teve 81,5 cladódios aos 24 meses após o plantio e justificaram este resultado à característica de crescimento de plantas do gênero Nopalea com elevado número de cladódios por planta, porém com baixo peso de cladódios.…”
Section: Massa De Forragem T De Mv/haunclassified
“…Cactus pear plant spacing has been studied in order to find an arrangement of plants that best suits the production systems (Oliveira Júnior et al, 2009). According to Silva et al (2014) and Cavalcante et al (2014), this species increases the yield with higher plant density.…”
Section: Introductionmentioning
confidence: 99%